COST EFFECTIVE AND SIMPLE METHOD FOR ROUTINE ANALYSIS OF ZIDOVUDINE AND LAMIVUDINE IN TABLET DOSAGE FORM BY RP – HPLC - RICHA. A. DAYARAMANI,; PARESH U PATEL, (International Journal of Pharma and Bio Sciences, 2015)
The objective of the current study is to develop a validated RP- HPLC method for the simultaneous estimation of Zidovudine1 and Lamivudine2 in tablet dosage form. The method follows sample preparation step followed by separation on Phenomenex C18 column (250 x 4.6mm id, 5 μm particle size utilizing Shimadzu HPLC (LC-10AT VP) equipped with UV-Visible and PDA detector. The mobile phase was prepared by mixing methanol, acetonitrile and water in the ratio of 60:20:20v/v/v. The eluted peaks were detected by photo diode array (PDA) detector at a wavelength of 265nm. The method was validated with respect to linearity, accuracy, precision, and robustness. The utility of the procedure was verified by its application to formulations and it was found that the developed method is fast, accurate, precise, selective, reproducible and cost effective and can be used for the routine laboratory analysis of tablet dosage form in institutions and industries.